Genetics of muscle strength and power: Polygenic profile similarity limits skeletal muscle performance - Hughes, D. C.; Day, S. H.; Ahmetov, I. I.; Williams, A. G. (Journal of Sports Sciences, 2011)
Environmental and genetic factors influence muscle function, resulting in large variations in phenotype between individuals. Multiple genetic variants (polygenic in nature) are thought to influence exercise-related phenotypes, yet how the relevant polymorphisms combine to influence muscular strength in individuals and populations is unclear. In this analysis, 22 genetic polymorphisms were identified in the literature that have been associated with muscular strength and power phenotypes. Using typical genotype frequencies, the probability of any given individual possessing an "optimal" polygenic profile was calculated as 0.0003% for the world population. Future identification of additional polymorphisms associated with muscular strength phenotypes would most likely reduce that probability even further. To examine the genetic potential for muscular strength within a human population, a "total genotype score" was generated for each individual within a hypothetical population of one million. The population expressed high similarity in polygenic profile with no individual differing by more than seven genotypes from a typical profile. Therefore, skeletal muscle strength potential within humans appears to be limited by polygenic profile similarity. Future research should aim to replicate more genotype-phenotype associations for muscular strength, because only five common genetic polymorphisms identified to date have positive replicated findings.